Stratigraphy and geochemistry of the Makganyene formation, Transvaal supergroup, Northern Cape, South Africa - Polteau, Stéphane (Rhodes University, Faculty of Science, Department of Geology, 2001)
The Makganyene Formation forms the base of the Postmasburg Group in the Transvaal Supergroup of the Northern Cape Province. The Makganyene Formation has diamictite as the main rock type, but siltstone, sandstone, shale, and iron-formations are also present. A glacial origin has been proposed in the past due to the presence of dropstones, faceted and striated pebbles. Typically, the Makganyene Formation contains banded iron-formations interbedded with clastic rocks (shale, siltstone, sandstone and diamictites) at the contact with the underlying iron-formations. This transitional zone is generally overlain by massive or layered diamictites which contain poorly sorted clasts (mainly chert) within a shaly matrix. Striated pebbles have been found during field work, and dropstones have been observed in diamictites and banded iron-formations during the study. The top of the Makganyene Formation contains graded cycles interbedded with diamictites and thin layers of andesitic lavas from the Ongeluk Formation. The basal contact of the Makganyene Formation with the underlying Koegas Subgroup was described as unconformable by previous workers. However field work localised in the Rooinekke area shows a broadly conformable and interbedded contact with the underlying Koegas Subgroup. As described above, banded iron-formations are interbedded with the clastic rocks of the Makganyene Formation. Moreover, boreholes from the Sishen area display the same interbedding at the base of the Makganyene Formation. This suggests that no significant time gap is present in the whole succession between the Ghaap and Postmasburg Group. The Transvaal Supergroup in the Northern Cape displays the following succession : carbonates-BIFs-diamictites/ lava-BIFs-carbonates. The Makganyene Formation is thus at the centre of a symmetrical lithologic succession. Bulk rock compositions show that the diamictites have a similar composition to banded iron-formation with regard to their major element contents. Banded iron-formations acted as a source for the diamictites with carbonates and igneous rocks representing minor components. Differences in bulk composition between the Sishen and Matsap areas emphasize that the source of the diamictite was very localised. The Chemical Index of Alteration (CIA) has been calculated, but since the source dominant rock was iron-formation, this index cannot be usefully applied to the diamictites. ACN, A-CN-K, and A-CNK-FM diagrams confer a major importance in sorting processes due to the separation between the fine and coarse diamictites. The interbedded iron-formations display little clastic contamination indicating deposition in clear water conditions. However, dropstones are present in one borehole from the Matsap area, indicating that iron-formation took place under ice cover, or at least under icebergs. Stable isotope studies show that the iron-formations, interbedded towards the base of the Makganyene Formation, have similar values to the iron-formations of the Koegas Subgroup. As a result of the above observations, new correlations are proposed in this study, relating the different Transvaal Supergroup basins located on the Kaapvaal Craton. The Pretoria Group of the Transvaal Basin has no correlative in the Griqualand West Basin, and the Postmasburg Group of the Northern Cape Basin has no lateral equivalent in the Transvaal Basin. These changes have been made to overcome problems present in the current correlations between those two basins. The Makganyene Formation correlates with the Huronian glaciations which occurred between 2.4 and 2.2 Ga ago in North America. Another Precambrian glaciation is the worldwide and well-studied Neoproterozoic glaciation (640 Ma). At each of these glaciations, major banded iron-formation deposition took place with associated deposition of sedimentary manganese in post-glacial positions. The central position of the Makganyene Formation within the Transvaal Supergroup in the Northern Cape emphasizes this glacial climatic dependence of paleoproterozoic banded iron-formation and manganese deposition. However these two Precambrian glaciations are interpreted in paleomagnetic studies as having occurred near to the equator. The controversial theory of the Snowball Earth has been proposed which proposes that the Earth was entirely frozen from pole to pole. Results from field work, sedimentology, petrography and geochemistry were integrated in a proposed depositional model of the Makganyene Formation occurring at the symmetrical centre of the lithologic succession of the Transvaal Supergroup. At the beginning of the Makganyene glaciation, a regression occurred and glacial advance took place. The diamictites are mostly interpreted as being deposited from wet-based glaciers, probably tidewater glaciers, where significant slumping and debris flows occurred. Any transgression would cause a glacial retreat by rapid calving, re-establishing the chemical sedimentation of banded iron-formations. These sea-level variations are responsible for the interbedding of these different types of rocks (clastic and chemical). The end of the Makganyene glacial event is characterised by subaerial eruptions of andesitic lava of the Ongeluk Formation bringing ashes into the basin. Banded iron-formation and associated manganese accumulations are climate-dependant. Glacial events are responsible for the build up of metallic ions such as iron and manganese in solution in deep waters. A warmer climate would induce a transgression and precipitation of these metallic ions when Eh conditions are favourable. In the Transvaal Supergroup, the climatic variations from warm to cold, and cold to warm are expressed by the lithologic succession. The warm climates are represented by carbonates. Cold climates are represented by banded iron-formations and the peak in cold climate represented by the diamictites of the Makganyene Formation. These changes in climate are gradual, which contradict the dramatic Snowball Earth event: a rapid spread of glaciated areas over low-latitudes freezing the Earth from pole-to-pole. Therefore, to explain low-latitude glaciations at sea-level, a high obliquity of the ecliptic is most likely to have occurred. This high obliquity of the ecliptic was acquired at 4.5 Ga when a giant impactor collided into the Earth to form the Moon. Above the critical value of 54Â° of the obliquity of the ecliptic, normal climatic zonation reverts, and glaciations will take place preferentially at low-latitudes only when favourable conditions are gathered (relative position ofthe continents and PC02 in the atmosphere).
Keywords: Geology, Stratigraphic -- South Africa -- Northern Cape; Geochemistry -- South Africa -- Northern Cape